Wide Range Variable Voltage Transformerless DC Power Supply Using TRIAC - Augustinus Sujono; Feri Adriyanto; Hari Maghfiroh; Joko Slamet Saputro; Agus Ramelan (Universitas Sebelas Maret (UNS), 2020)
Variable voltage DC power supply that has wide range of power, lightweight and inexpensive is quite difficult to obtain. This research designs and tests a DC power supply without a transformer using switching technology that utilizes TRIAC. The 220 Volt AC power source is converted to DC electricity by the method of cutting off some AC waves signal, using TRIAC, and then rectifying it with diodes and filters. DIAC functions as a trigger TRIAC at the specified time, by turning the variable resistor. The test results show that the output DC power voltage can be adjusted from 5 Volts to 75 Volts by adjusting the DIAC resistance and the load resistance. The results of the series image characteristics are given 2-dimensional and 3-dimensional graphics.